EFL Learners’ Beliefs and Practices on Informal Digital Learning of English beyond Classroom - Arif Nugroho; Yunika Triana (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThe present-day English language learning is characterized by educational potentials of digital technology for informal learning context. However, research examining EFL learners’ characteristics on self-directed use of digital devices for language learning remains a paucity of evidence. Addressing this current issue, the present study aims to shed some light on English language learners’ beliefs and practices on informal digital learning of English beyond classroom. A total of 117 Indonesian EFL learners participated in this study through a 5-point Likert-scale survey and semi-structured interview. The results revealed the disparity between the EFL learners’ beliefs and practices on informal digital learning of English. These EFL learners surely believed that informal digital learning activities could significantly enhance the target language skills, but they slightly engaged in digital learning activities beyond the classroom schedule. The results of semi-structured interviews further delineated that use of native languages in their social circle relationships and limitations of the digital devices used became particular reasons for this circumstance. The results contribute to the realm of English language teaching to reach the possible synchronicity between teacher-designed in-class and out-class digital learning activities and students’ language learning styles and preferences to achieve the success of target language learning.ABSTRAKPembelajaran bahasa Inggris masa kini bercirikan potensi pendidikan teknologi digital untuk konteks pembelajaran informal. Namun, penelitian yang meneliti karakteristik pelajar EFL tentang penggunaan perangkat digital secara mandiri untuk pembelajaran bahasa masih tetap kekurangan bukti. Mengatasi masalah saat ini, penelitian ini bertujuan untuk menjelaskan keyakinan dan praktik pembelajar bahasa Inggris tentang pembelajaran digital informal bahasa Inggris di luar kelas. Sebanyak 117 pelajar EFL Indonesia berpartisipasi dalam penelitian ini melalui survei skala Likert 5 poin dan wawancara semi terstruktur. Hasilnya mengungkapkan perbedaan antara keyakinan dan praktik pelajar EFL pada pembelajaran digital informal bahasa Inggris. Pembelajar EFL ini pasti percaya bahwa kegiatan pembelajaran digital informal dapat secara signifikan meningkatkan keterampilan bahasa target, tetapi mereka sedikit terlibat dalam kegiatan pembelajaran digital di luar jadwal kelas. Hasil wawancara semi-terstruktur lebih lanjut menggambarkan bahwa penggunaan bahasa asli dari hubungan lingkaran sosial mereka dan keterbatasan perangkat digital yang digunakan menjadi alasan khusus untuk keadaan ini. Hasilnya berkontribusi pada ranah pengajaran bahasa Inggris untuk mencapai kemungkinan sinkronisitas antara kegiatan pembelajaran digital di dalam dan di luar kelas yang dirancang guru dan gaya dan preferensi belajar bahasa siswa untuk mencapai keberhasilan pembelajaran bahasa target.